The Correlation of EMMPRIN and EGFR Overexpression toward Muscle Invasiveness in Urothelial Carcinoma of Bladder - Leonita Agustin Hambalie, Leonita
Abstract and Figures Urothelial carcinomas represent 90% of all primary bladder cancers. Muscle invasion is a critical prognostic determinant in urothelial carcinoma. The overexpression of EMMPRIN and EGFR was found in urothelial carcinoma. The association between the two markers has not been reported in urothelial carcinoma, therefore we aimed to analyze the expression of EMMPRIN and EGFR and investigate their association with urothelial carcinoma invasiveness. Paraffin-embedded tissues were obtained from 54 urothelial carcinoma patients which then underwent immunohistochemistry staining for EMMPRIN and EGFR antibody. The comparison of EMMPRIN and EGFR expression was tested using the Mann Whitney U test. The correlation was analyzed using the Spearman test. Results showed a significant difference of EMMPRIN expression between non-muscle-invasive and muscle-invasive bladder cancer (p = 0.000), and EMMPRIN expression was significantly correlated with the muscle invasion (r s = 0.481, p = 0.000). A significant difference of EGFR expression between the non-muscle-invasive and muscle-invasive bladder cancer was also found (p = 0.020), and EGFR expression was significantly correlated with the muscle invasion (r s = 0.319, p = 0.019). The expression of EMMPRIN was positively correlated with EGFR in urothelial carcinoma (r s = 0.322, p = 0.018). The expression of EMMPRIN and EGFR are two potential biomarkers for urothelial carcinoma invasiveness which may be helpful to differentiate between muscle-invasive and non-muscle-invasive bladder cancer.